KALIMANTAN BORDER ISSUES AND INDONESIA'S BORDER DIPLOMACY TOWARDS MALAYSIA - Ari Bayu Purnama; Muhammad Ridha Iswardhana (Natapraja, 2022)
This article aims to explain Indonesia's border diplomacy towards Malaysia regarding cross-border issues for the 2014-2020 period. In this case, there are often cases of disputes over territorial boundaries and social problems in border areas. To overcome this, Indonesia and Malaysia created the Malindo Social Security Cooperation (Sosek Malindo) and the Joint Indonesia Malaysia (JIM). This is following Indonesia's border diplomacy efforts which prove by the activities of annual meetings and sessions. The research method used a qualitative descriptive-analytical approach. The case analysis will explain the causes and effects of holding Indonesia-Malaysia border diplomacy based on secondary data. The author finds that various meetings and annual sessions of the two cooperation forums can resolve border disputes, illegal trade in goods and labor, and cross-border disputes related to the existence of Natural Resources. This research found that Indonesia-Malaysia border diplomacy in dealing with cross-border problems in 2014-2020 is carried out through the Malindo Social Security Cooperation (Sosek Malindo) and the Joint Indonesia Malaysia (JIM) cooperation. As a result, two segments of the national border were established at Simantipal River and Point C500-C600. Then in the case of PLBN development, Indonesia and Malaysia carried out border diplomacy through the Malindo Sosek Cooperation Forum in the form of the 35th and 37th meetings of KK/JKK Sosek Malindo and the 14th and 15th trials of Sekber KK/JKK Sosek Malindo.